Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1088/0031-8949/2009/t138/014009
|View full text |Cite
|
Sign up to set email alerts
|

Fuel removal from tile gaps with oxygen discharges: reactivity of neutrals

Abstract: Carbon removal in so-called remote areas, where no energetic species can reach the surface, is investigated with low-temperature glow discharges in pure oxygen. Plasma-deposited amorphous hydrogenated carbon thin films are used as a model system for redeposited films. Erosion measurements are performed on flat substrates as well as on two different 3D test structures. One design consists of 19 mm deep gaps with widths ranging from 0.5 to 4 mm to simulate ITER tile gaps. A second design consists of a flat box-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…This is not too surprising since an oxygen plasma is a source for species with a much higher reactivity than stable ground state oxygen molecules. Secondly, this value is also significantly lower than that found for oxygen glow discharge removal of plasma-deposited amorphous hydrogenated carbon (a-C:H) films in plasma-shaded areas (0.25 eV [12]). Thirdly, the 1.8 % a-C:W films has a higher apparent activation energy than the pure a-C film and shows, therefore, a larger resilience against oxidation than the pure C film.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…This is not too surprising since an oxygen plasma is a source for species with a much higher reactivity than stable ground state oxygen molecules. Secondly, this value is also significantly lower than that found for oxygen glow discharge removal of plasma-deposited amorphous hydrogenated carbon (a-C:H) films in plasma-shaded areas (0.25 eV [12]). Thirdly, the 1.8 % a-C:W films has a higher apparent activation energy than the pure a-C film and shows, therefore, a larger resilience against oxidation than the pure C film.…”
Section: Resultsmentioning
confidence: 63%
“…For example, ASDEX Upgrade showed that removal is very effective even at room temperature and similar results were obtained in TEXTOR and HT-7 for elevated temperatures [4][5][6][7][8]. Schwarz-Selinger et al [11,12] have recently shown that oxygen plasmas are very efficient for removal of hydrocarbon films which are a good model system for re-deposited carbon films in fusion devices. This is true not only for plasma exposed areas [11], but at elevated surface temperatures (> 400 K) also for areas which have no direct line of sight to the cleaning discharge such as, e.g., in tile gaps.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Gaps between castellation cells serve, however, as traps for the migrating impurities and co-deposited fuel, contributing to the safety problem of the tritium retention [1]. The efficiency of the fuel removal methods is restricted in gaps due to their geometry [2][3][4]. A dedicated campaign to study the mechanisms of fuel retention was performed in the Tore Supra tokamak, revealing the details of the asymmetry of the deposition in toroidal and poloidal gaps [5] and peculiarities of the co-deposition in gaps [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, increasing the substrate temperature to 200 • C or the current density did not convey any improvement of the cleaning rate in this region. Taking into account the expected enhancement of erosion rate by neutral species with temperature [47], channelling of the impinging ions by the local electric field self-generated within the gap [48] appears as the leading mechanism for the removal of these hard-to-reach deposits, in contradiction with our previous conclusions on this subject [40]. Therefore, plasma techniques implying the presence of energetic ions, such as dc GDs, not only would lead to enhanced rates by synergistic ion-radical effects but they could be strictly required if deposition at the gap bottom becomes an issue in a fusion reactor.…”
Section: Removal By O 2 N 2 Nh 3 and No 2 Plasmasmentioning
confidence: 99%